Evaluation of Pain and Tenderness in Endodontic Treatment of Deciduous Teeth using (LSTR) 3-Mix MP therapy - Ali, Mohammad; Moral, Ali Asgor; Quader, SM Abdul (Update Dental College Journal, 2018)
Aim and objective: The purpose of this study was to evaluate the prognosis of pain and tenderness in endodontic treatment of deciduous teeth using LSTR 3-MixMP therapy. Materials and method: The treatment was performed on selected 60 patients of 60 teeth which were divided into two groups; Group-A(n=30) and Group-B(n=30).In group-A patients were diagnosed initial pulpitis or reversible pulpitis (vital inflamed pulp) and in group-B patients were diagnosed as non-vital necrosed pulp with or without inter-radicular lesion. In both groups carious lesion and previ- ous restorative materials were removed and the cavity was prepared in such a way which was termed as “Medication cavity”. The cavity was cleaned and dried and then LSTR 3Mix MP therapy was placed at the orifice of root canals or on the bottom of the pulp chamber and then sealed with glass-ionomer cement and further reinforced with composite resin. Resolution of clinical signs and symptoms; pain and tenderness to percussion were evaluated at one week, one month, six months and one year inter- val. Result: In all cases clinical symptoms such as pain and tenderness to percussion disappeared after treatment in both groups but group B showed better clinical success. Finally all the cases were evalu- ated as successful. Conclusion: Based on the present study it can be concluded that endodontically involved deciduous teeth in both vital (inflamed) and non-vital teeth associated with pain and tenderness were treated successfully by LSTR 3-Mix MP therapy. Update Dent. Coll. j: 2017; 7 (2): 09-14